2005
DOI: 10.1080/13693780400029247
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular and extracellular growth ofAspergillus fumigatus

Abstract: Aspergillus fumigatus is a filamentous fungus that can cause a life-threatening systemic mycosis in immunocompromised patients. We have studied the growth of A. fumigatus inside cultured cells, and the extracellular growth requirements (in serum). We measured the uptake of bound conidia by the cultured human type II pneumocyte cell line (A549) and a mouse macrophage cell line (J774). The extent of internalization was determined using a nystatin protection assay and by confocal microscopy. Both assays showed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 24 publications
1
34
0
Order By: Relevance
“…Aspergillus fumigatus is an opportunistic pathogen responsible for a number of respiratory diseases in normal hosts and severe invasive infections in immunocompromised patients (Latgé & Calderone, 2002). Although in this instance alveolar macrophages and neutrophils are known to phagocytose and kill Aspergillus conidia, a small percentage may be able to survive within these cells; moreover, it has been reported that fungal conidia may attempt to escape from professional phagocytes by invading epithelial and endothelial cells (Ibrahim-Granet et al, 2003;Wasylnka & Moore, 2003;Wasylnka et al, 2005). Furthermore, Aspergillus infections can cause significant cell injury during invasion, producing tissue damage that can induce host cell defences, with escape into normally nonphagocytic host cells by induction of fungal cell uptake serving as a mechanism to avoid such defences (Lopes Bezerra & Filler, 2004;Filler & Sheppard, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Aspergillus fumigatus is an opportunistic pathogen responsible for a number of respiratory diseases in normal hosts and severe invasive infections in immunocompromised patients (Latgé & Calderone, 2002). Although in this instance alveolar macrophages and neutrophils are known to phagocytose and kill Aspergillus conidia, a small percentage may be able to survive within these cells; moreover, it has been reported that fungal conidia may attempt to escape from professional phagocytes by invading epithelial and endothelial cells (Ibrahim-Granet et al, 2003;Wasylnka & Moore, 2003;Wasylnka et al, 2005). Furthermore, Aspergillus infections can cause significant cell injury during invasion, producing tissue damage that can induce host cell defences, with escape into normally nonphagocytic host cells by induction of fungal cell uptake serving as a mechanism to avoid such defences (Lopes Bezerra & Filler, 2004;Filler & Sheppard, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…42 Irrespective of whether IDO itself may contribute to the antimicrobial innate function of ECs, our data indicate an important role for the MyD88 pathway in ECs in the control of fungal growth, a finding suggesting the possible antifungal effector activity of ECs. In this regard, despite the fact that airways ECs phagocytose Aspergillus conidia, 16,17 the ability of conidia to survive in ECs 17 was taken to indicate airways ECs as a possible fungus reservoir. More recently, ECs were found to respond to Aspergillus conidia via MyD88-dependent and -independent pathways 18 and by upregulating antimicrobial peptides 43,44 endowed with antifungal activity.…”
Section: Discussionmentioning
confidence: 99%
“…This has lent to the credence that ECs may serve as reservoirs for immune evasion. 16,17 However, respiratory ECs also sense germinating conidia through MyD88-dependent and -independent pathways. 18 Of interest, IDO overexpression from the airway ECs was found to restrain CD4 1 T-cell activation to the fungus, an activity that was nevertheless dispensable in the presence of IDO-expressing DCs.…”
Section: Dendritic Cells (Dcs) Orchestrate the Adaptive Immune Responmentioning
confidence: 99%
“…is not well defined, and the clinical relevance of antifungal ELF concentrations is unknown. In vitro studies demonstrate a propensity for the conidiae and hyphae of Aspergillus fumigatus to invade and germinate in human pneumocytes (6,17). Thus, the sites of pulmonary aspergillosis likely include not only the ELF but also alveolar macrophages, pulmonary epithelial cells, and the interstitial fluid of lung tissue.…”
mentioning
confidence: 99%